The Physics of the B Factories - Thomas Mannel (Springer Nature, 2017)
This comprehensive work thoroughly introduces and reviews the set of results from Belle and BaBar - after more than two decades of independent and complementary work - all the way from the detectors and the analysis tools used, up to the physics results, and the interpretation of these results. The world's two giant B Factory collaborations, Belle at KEK and BaBar at SLAC, have successfully completed their main mission to discover and quantify CP violation in the decays of B mesons. CP violation is a necessary requirement to distinguish unambiguously between matter and antimatter. The shared primary objective of the two B Factory experiments was to determine the shape of the so-called unitarity triangle, an abstract triangle representing interactions of quarks, the elementary constituents of matter. The area of the triangle is a measure of the amount of CP violation associated with the weak force. Many other measurements have been performed by the B Factories and are also discussed in this work.